Educated women participate in social and cultural development: Anthropological study from the viewpoint of graduate students at the University of Baghdad / College of Arts - Haider, Hilal Abdul-Sadah (Al-Adab Journal, 2019)
The goal of the topic is to address one of the problems that Iraqi women suffer from, This is the extent to which educated women participate in social and cultural development projects, What is the role that it plays in that participation by being the largest half of society, So was the woman able to be active in entering the battlefield of conflict with men and taking the initiative and to be challenging to her cultural and social reality, or does she still suffer from male domination and subjugation to him through social norms that may be in large part depriving women of a large part of their rights, Did the educated woman manage to apply the knowledge and knowledge she learned on the ground, and did she have a role in raising her standard of living and social and other matters related to this topic, As Iraqi women are an inherent partner to men in various areas of daily life that appear in the behavior of members of society, Therefore, the participation of women in social and cultural development is a basic requirement recognized and guaranteed by the Iraqi constitution and law and desired by society. The research aimed to know the tendencies of Iraqi women to participate in social and cultural development and what are the elements that hinder and affect such participation, such as social and cultural. Therefore, the research was divided into two topics: the first topic touched on the theoretical side and related concepts related to the subject of the research. The second topic dealt with the field procedures for research. The researcher recommends governmental institutions, NGOs, civil society organizations, and media in all its forms to support the real participation of Iraqi women in social and cultural development processes.